Large-scale synaptic dynamics drive the reconstruction of binocular circuits in mouse visual cortex - Katya Tsimring; Kyle R. Jenks; Claudia Cusseddu; Greggory R. Heller; Jacque Pak Kan Ip; Julijana Gjorgjieva; Mriganka Sur (Nature Communications)
Abstract In the binocular primary visual cortex, visual experience   shapes neuronal responses to the contralateral and ipsilateral eye during a critical period in postnatal development. The synaptic changes that underlie the construction of binocular circuits are unknown. Using chronic in vivo two-photon imaging to record the somata and excitatory synaptic inputs onto dendritic spines of identified layer 2/3 neurons in mouse binocular visual cortex, we report that spines experience significant turnover and eye-specific remapping of their visual responses during the critical period. Spine retention is strongly linked to their calcium activity, particularly in response to the soma’s preferred visual stimulus. Furthermore, spine responses  become more correlated to those of their neighbors after development. Using a single-neuron model, we show that Hebbian and heterosynaptic mechanisms plausibly underlie the retention and localized organization of synaptic inputs. Our results underscore the profound dynamics at individual synapses and the fundamental synaptic mechanisms that shape the development of visual cortical neurons.